Rancang Bangun Alat Pemberi Pakan Ternak Ikan Otomatis Berbasis Mikrokontroler Arduino, Sensor Ultrasonik dan Module Sim800l - Alvin Fuadi; Rahmat W Sembiring; Sumarno Sumarno; Indra Gunawan; Zulaini Masruro Nasution (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Feed is the food intake needed by fish farm animals, feed serves as a source of energy or energy and is needed for growth and survival. Fish animal feed consists of two types, namely natural feed and artificial feed. Natural feed is food that comes from nature in the form of life and is difficult to develop. Meanwhile, artificial feed is feed made from several processed ingredients that meet the nutritional content needed by fish. One of the artificial fish feed that is commonly used and often encountered is pellets. Currently, fish feed is still done manually and the process is still constrained by its ineffective use of time. Therefore, an automatic fish feeder based on Arduino Uno was designed to help fish farmers to feed their fish. With the microcontroller-based Arduino design, the Arduino is assisted with the Sim800l Module which is useful as a controller with an SMS message in order to run commands that have been programmed and assisted by the Ultrasonic sensor as a feed stock check when the fish feed stock has run out and classify it by sending notification messages in the form of SMS . Based on the research conducted, the results show that the tool will work if it gets a command message via the number planted on the Sim800l Module and works to move the Servo Motor to open and close the valve on the container for 3 seconds. After the Servo Motor opens and closes the valve on the container again, the Sim800l Module will send a notification message that the feed has been completed. In this case the Ultrasonic sensor detects the pellet container when the feed stock runs out, the Buzzer will sound and the sensor sends a signal to the Sim800l Module and after that the Sim800l Module will send a notification message to the user number that the feed stock is running out.